2000
DOI: 10.1097/00005392-200009020-00046
|View full text |Cite
|
Sign up to set email alerts
|

The Long-Term Followup of Newborns With Severe Unilateral Hydronephrosis Initially Treated Nonoperatively

Abstract: Unilateral newborn hydronephrosis appears to be relatively benign and in most instances dilatation and renal function improve with time. However, close followup is necessary to identify the subgroup of less than 25% of infants with obstruction because prompt pyeloplasty will prevent permanent loss of renal function. Standard tests for assessing obstruction in older patients appear to be invalid in infants because prolonged half-time and/or high grade hydronephrosis is neither an indicator of obstruction or sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
130
3
11

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(147 citation statements)
references
References 16 publications
3
130
3
11
Order By: Relevance
“…Maternal ultrasonography detects fetal hydronephrosis, leading to the diagnosis of PUJ obstruction postnatally in 0.2-0.4% of cases [1][2][3][4][5]; PUJ obstruction requires surgery in 15-30% of affected children [6][7][8][9][10][11][12][13][14]. Controversy continues on the optimal timing of the surgical correction in these children with antenatally detected hydronephrosis [7,8,[14][15][16][17]. Children with an antenatal diagnosis of PUJ obstruction reportedly show a significant improvement in renal function after surgery compared with those who are diagnosed and operated much later because of their clinical symptoms [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maternal ultrasonography detects fetal hydronephrosis, leading to the diagnosis of PUJ obstruction postnatally in 0.2-0.4% of cases [1][2][3][4][5]; PUJ obstruction requires surgery in 15-30% of affected children [6][7][8][9][10][11][12][13][14]. Controversy continues on the optimal timing of the surgical correction in these children with antenatally detected hydronephrosis [7,8,[14][15][16][17]. Children with an antenatal diagnosis of PUJ obstruction reportedly show a significant improvement in renal function after surgery compared with those who are diagnosed and operated much later because of their clinical symptoms [12].…”
Section: Introductionmentioning
confidence: 99%
“…In early published series, King et al [6] encouraged immediate pyeloplasty, regardless of renal function, after obstruction was detected by diuretic renography. In recent years, Koff et al [7,9,15] suggested that unilateral antenatal hydronephrosis caused by PUJ obstruction is a relatively benign condition requiring surgery only in highly selected cases. Despite numerous studies it remains unclear what improvement in renal function can be expected after pyeloplasty, and which patients will benefit from expectant management; this paper addresses these issues.…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that the majority of infants are asymptomatic, and it may take upwards of 3 years for a kidney to declare itself. In observational studies, the disease has been shown to resolve spontaneously over time in an ill-defined but well-documented group of patients [2]. In the majority of infants, imaging or clinical parameters do not discriminate between those who are likely to progress and those who are not.…”
mentioning
confidence: 99%
“…However, attitudes towards surgery still remain extremely heterogeneous, varying from a systematic surgical approach in the early months of life [9,10] up to a similar systematic conservative follow-up [11]. An absence of well-controlled prospective studies in this field is at least partly responsible for this situation.…”
mentioning
confidence: 99%
“…Moreover, no single controlled study is available showing that the kidney with poor function is more at risk of deterioration than the kidney with normal split function [8,13]. Similarly, it has been shown that poor renal drainage does not necessarily represent per se a risk of renal deterioration [5,11].…”
mentioning
confidence: 99%